Determination of Tanin Extract of Belimbing Wuluh Leaves (Averrhoa Bilimbi L.) by Uv-Vis Spectroscopy Methods - Ririen Hardani; Muhammad F. Hardani; Baharuddin Hamzah; Sindy T. Tamala (Jurnal Akademika Kimia, 2025)
Wuluh star fruit plant (Averrhoa bilimbi L.) was a traditional medicinal plant that was rarely utilized as a natural medicine and contained many secondary metabolite compounds, one of which was tannin. This study aimed to determine the type of tannin and the amount of tannin content in belimbing wuluh leaves. Wuluh star fruit leaf powder was extracted by the maceration method using 96 % ethanol solvent, and then the filtrate was concentrated by rotary evaporator. Identification of tannin types in the extract was performed using CH3COOH 10 %, (Pb(CH3COO)2) 10 %, HCl, FeCl3, and KBr. For analysis of tannin content, Folin-Ciocalteau reagent and 15 % Na2CO3 solution were added, and then analyzed using UV-Vis spectrophotometry at a wavelength of 765 nm. The results of the identification of tannin types showed that belimbing wuluh leaves included condensed tannins, and the results of the analysis showed that the tannin content was 7.282 mg/g extract.